2021
DOI: 10.3390/molecules26185623
|View full text |Cite
|
Sign up to set email alerts
|

Cerium-Promoted Ginsenosides Accumulation by Regulating Endogenous Methyl Jasmonate Biosynthesis in Hairy Roots of Panax ginseng

Abstract: Among rare earth elements, cerium has the unique ability of regulating the growth of plant cells and the biosynthesis of metabolites at different stages of plant development. The signal pathways of Ce3+-mediated ginsenosides biosynthesis in ginseng hairy roots were investigated. At a low concentration, Ce3+ improved the elongation and biomass of hairy roots. The Ce3+-induced accumulation of ginsenosides showed a high correlation with the reactive oxygen species (ROS), as well as the biosynthesis of endogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Ginsenosides have a variety of pharmacological activities, including preventing neurological diseases, increasing immune function, delaying aging, and improving sleep (Kim et al, 2018 ; Jin et al, 2021 ). Although the importance and yield of ginsenosides have been widely studied, the yield of ginsenosides remains low (Zhang et al, 2021a ; He et al, 2022 ). Therefore, it is urgent to optimize ginseng cultivation techniques and increase ginsenoside yields to meet medicinal needs.…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenosides have a variety of pharmacological activities, including preventing neurological diseases, increasing immune function, delaying aging, and improving sleep (Kim et al, 2018 ; Jin et al, 2021 ). Although the importance and yield of ginsenosides have been widely studied, the yield of ginsenosides remains low (Zhang et al, 2021a ; He et al, 2022 ). Therefore, it is urgent to optimize ginseng cultivation techniques and increase ginsenoside yields to meet medicinal needs.…”
Section: Introductionmentioning
confidence: 99%
“…Although there were reports of ginseng callus culture in the 1960s, in vitro culture of ginseng cell are relatively delayed due to the slow growth and low content of target active ingredients in ginseng callus [33,34]. While Research on hairy root of ginseng has made great progress like regulating endogenous methyl jasmonate biosynthesis [35,36].…”
Section: Application Trends Of Industrial Output In Plants Cell Culturesmentioning
confidence: 99%
“…However, plant secondary metabolites are regulated by many enzymes and genes owing to their diversity and complex synthesis mechanisms (Pickett, 2014). Therefore, the in-depth exploration of metabolic pathways is key to clarifying the molecular mechanism of the biosynthesis of medicinal substances, improving the quality of medicinal materials, and solving the shortage of medicinal plant resources (Zhang et al, 2021). This study found that fertilizer application can induce changes in enzymes and gene levels in plants, promote the accumulation of secondary metabolites, and thus enhance plant growth and competitive advantage in the natural environment (Krausfeldt et al, 2019).…”
Section: Npk Pharmacodynamic Components Key Enzymes and Genes Interac...mentioning
confidence: 99%